Costs variations for percutaneous nephrolithotomy in the U.S. from 2003–2015: A contemporary analysis of an all-payer discharge database - Leow, Jeffrey J.; Valiquette, Anne-Sophie; Chung, Benjamin I.; Chang, Steven L.; Trinh, Quoc-Dien; Korets, Rus; Bhojani, Naeem (Canadian Urological Association Journal, 2018)
Introduction: We sought to evaluate population-based cost variations and predictors of outlier costs for percutaneous nephrolithotomy (PCNL) in the U.S. Methods: Using the Premier Healthcare Database, we identified all patients diagnosed with kidney/ureter calculus who underwent PCNL from 2003–2015. We evaluated 90-day direct hospital costs, defining high- and low-cost surgery as those >90th and <10th percentile, respectively. We constructed a multilevel, hierarchical regression model and calculated the pseudo-R2 of each variable, which translates to the percentage variability contributed by that variable on 90-day direct hospital costs. Results: A total of 114 581 patients underwent PCNL during the 12-year study period. Mean cost in the low-cost group was 5787 (95% confidence interval [CI] 5716–5856) vs. 38 590 (95% CI 37 357–39 923) in the high-cost group. Cost variations were substantially impacted by patient (63.7%) and surgical (18.5%) characteristics and less so by hospital characteristics (3.9%). Significant predictors of high costs included more comorbidities (≥2 vs. 0: odds ratio [OR] 1.81; p=0.01) and hospital region (Northeast vs. Midwest: OR 2.04; p=0.03). Predictors of low cost were hospital bed size of 300–499 beds (OR 1.35; p<0.01) and urban hospitals (OR 2.77; p=0.01). Factors less likely to be associated with lowcost PCNL were more comorbidities (Charlson Comorbidity Index [CCI] ≥2: OR 0.69; p<0.0001), larger hospitals (OR 0.61; p=0.01), and teaching hospitals (OR 0.33; p<0.0001). Conclusions: Our contemporary analysis demonstrates that patient and surgical characteristics had a significant effect on costs associated with PCNL. Poor comorbidity status contributed to high costs, highlighting the importance of patient selection.